Digital Public Relations in School-Based Health Campaigns: A Systematic Literature Review toward a Hybrid Engagement Model in the Indonesian Context - Wiratri Anindhita; Muria Putriana; Wina Puspita Sari (INJECT (Interdisciplinary Journal of Communication), 2026)
This study explores the role of digital public relations in school-based health campaigns and addresses the lack of an integrative framework to link communication, engagement, and digital interaction. The study employed a qualitative Systematic Literature Review (SLR) using the PRISMA framework. A total of 45 peer-reviewed articles published between 2015 and 2024 were analyzed. The study combined bibliometric analysis using VOSviewer and thematic synthesis through open, axial, and selective coding. The findings revealed three key gaps: (1) conceptual fragmentation between communication and engagement theories, (2) limited contextual exploration in developing countries like Indonesia, and (3) the methodological dominance of empirical studies without conceptual integration. The results also indicated that communication practices were largely one-way, engagement was reduced to measurable metrics, and digital media was used primarily as a delivery tool rather than an interactive platform. This study proposed a Hybrid Engagement Model comprising institutional communication, participatory engagement, and digital interaction that could contribute to education and communication research by positioning schools as active communication hubs and promoting digitally integrated participatory health campaigns.